The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1142/s0218271815500212
|View full text |Cite
|
Sign up to set email alerts
|

Vaidya solution in general covariant Hořava–Lifshitz gravity with the minimum coupling and without projectability: Infrared limit

Abstract: In this paper, we have studied nonstationary radiative spherically symmetric spacetime, in general covariant theory (U (1) extension) of the Hořava-Lifshitz gravity with the minimum coupling, in the post-newtonian approximation (PPN), without the projectability condition and in the infrared limit. The Newtonian prepotential ϕ was assumed null. We have shown that there is not the analogue of the Vaidya's solution in the Hořava-Lifshitz Theory (HLT) with the minimum coupling, as we know in the General Relativity… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The junction conditions across the surface of a collapsing star were derived under the (minimal) assumption that the junctions must be mathematically meaningful in terms of distribution theory. Lately, gravitational collapse in this setup was investigated and various solutions were constructed [141][142][143].…”
Section: B With Projectability and U(1) Symmetrymentioning
confidence: 99%
“…The junction conditions across the surface of a collapsing star were derived under the (minimal) assumption that the junctions must be mathematically meaningful in terms of distribution theory. Lately, gravitational collapse in this setup was investigated and various solutions were constructed [141][142][143].…”
Section: B With Projectability and U(1) Symmetrymentioning
confidence: 99%
“…In another recent paper, Goldoni et al (2015) [43], using again Lin at al. (2014) [41] approach, have also shown that there is not an analogy of the Vaidya's solution in Hořava-Lifshitz Theory (HLT) with the minimally coupling and without projectability, again as we know in GRT.…”
Section: Introductionmentioning
confidence: 99%